Receptor binding profiles and quantitative structure–affinity relationships of some 5-substituted-N, N-diallyltryptamines. Issue 3 (1st February 2016) - Cozzi, Nicholas V.; Daley, Paul F.
Graphical abstract: Abstract: N, N -Diallyltryptamine (DALT) and 5-methoxy- N, N -diallyltryptamine (5-MeO-DALT) are two tryptamines synthesized and tested by Alexander Shulgin. In self-experiments, 5-MeO-DALT was reported to be psychoactive in the 12–20 mg range, while the unsubstituted compound DALT had few discernible effects in the 42–80 mg range. Recently, 5-MeO-DALT has been used in nonmedical settings for its psychoactive effects, but these effects have been poorly characterized and little is known of its pharmacological properties. We extended the work of Shulgin by synthesizing additional 5-substituted-DALTs. We then compared them to DALT and 5-MeO-DALT for their binding affinities at 45 cloned receptors and transporter proteins. Based on in vitro binding affinity, we identified 27 potential receptor targets for the 5-substituted-DALT compounds. Five of the DALT compounds had affinity in the 10–80 nM range for serotonin 5-HT1A and 5-HT2B receptors, while the affinity of DALT itself at 5-HT1A receptors was slightly lower at 100 nM. Among the 5-HT2 subtypes, the weakest affinity was at 5-HT2A receptors, spanning 250–730 nM. Five of the DALT compounds had affinity in the 50–400 nM range for serotonin 5-HT1D, 5-HT6, and 5-HT7 receptors; again, it was the unsubstituted DALT that had the weakest affinity at all three subtypes. The test drugs had even weaker affinity for 5-HT1B, 5-HT1E, and 5-HT5A subtypes and little or no affinity for the 5-HT3 subtype. These compounds also had generally nanomolar affinities for adrenergic α2A, α2B, and α2C receptors, sigma receptors σ1 and σ2, histamine H1 receptors, and norepinephrine and serotonin uptake transporters. They also bound to other targets in the nanomolar-to-low micromolar range. Based on these binding results, it is likely that multiple serotonin receptors, as well as several nonserotonergic sites are important for the psychoactive effects of DALT drugs. To learn whether any quantitative structure–affinity relationships existed, we evaluated correlations among physicochemical properties of the congeneric 5-substituted-DALT compounds. The descriptors included electronic ( σp ), hydrophobic ( π ), and steric (CMR) parameters. The binding affinity at 5-HT1A, 5-HT1D, 5-HT7, and κ opioid receptors was positively correlated with the steric volume parameter CMR. At α2A, α2B, and α2C receptors, and at the histamine H1 receptor, binding affinity was correlated with the Hammett substituent parameter σp ; higher affinity was associated with larger σp values. At the σ2 receptor, higher affinity was correlated with increasing π . These correlations should aid in the development of more potent and selective drugs within this family of compounds.